Relative abundance of diatoms in a sediment core from Lake Pacú, lower Negro River, Central Amazonia, during the mid- to late Holocene - Rodrigues, Érika do Socorro Ferreira; Yao, Qiang (PANGAEA, 2025)
This dataset contains the relative abundance of diatom taxa identified in 68 sediment samples collected at 0.10 m intervals from core NGR07, from Lake Pacú, in the lower Negro River region of the Central Amazonia. The diatom assemblages were analyzed to reconstruct changes in aquatic conditions associated with flood pulse oscillations during the mid- to late Holocene. Approximately 500 valves were counted per sample using light microscopy, and taxa were identified based on microstructural features, supported by regional diatom atlases. The dataset includes both periphytic and planktonic forms, reflecting lake-level variations since the mid-Holocene. Diatom diagrams and zonations were generated using Tilia and CONISS software.
Keywords: Amazon Basin; Diatom assemblage; limnology; pollen and spores; reconstructing vegetation change